RELIGIOUS EXPERIENCE AND REVELATION - Mampra, Thomas (Journal of Dharma, 1988)
Revelation is always understood in contrast to man’s natural religious experience. The problem whether there is real opposition between natural and revealed religious experience is often discussed in the Christian theological tradition, especially in the context of the comparative study of religions. In this paper I propose to examine S. Radhakrishnan’s attempt to reconcile the conflict between natural religious experience and revelation. The main ideas of the author are brought under four main heads: 1) Religious experience; 2) Its Nature; 3) The content of Religious Experience.